2017
DOI: 10.3389/fmicb.2017.01328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Components Involved in Cyclic Di-AMP Signaling in Mycoplasma pneumoniae

Abstract: Bacteria often use cyclic dinucleotides as second messengers for signal transduction. While the classical molecule c-di-GMP is involved in lifestyle selection, the functions of the more recently discovered signaling nucleotide cyclic di-AMP are less defined. For many Gram-positive bacteria, c-di-AMP is essential for growth suggesting its involvement in a key cellular function. We have analyzed c-di-AMP signaling in the genome-reduced pathogenic bacterium Mycoplasma pneumoniae. Our results demonstrate that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 47 publications
2
57
0
2
Order By: Relevance
“…Several different families of DACs have been identified, which all differ in their additional regulatory domain (Commichau et al, ; Corrigan & Gründling, ). So far, members of four bacterial DAC classes have been characterized in more detail: DisA (Witte et al, ), DacA/CdaA (Rosenberg et al, ), DacB/CdaS (Mehne et al, ), and CdaM (Blötz et al, ). Additionally, DAC activity has been demonstrated for a representative of the archaeal DacY/CdaZ class (Kellenberger et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different families of DACs have been identified, which all differ in their additional regulatory domain (Commichau et al, ; Corrigan & Gründling, ). So far, members of four bacterial DAC classes have been characterized in more detail: DisA (Witte et al, ), DacA/CdaA (Rosenberg et al, ), DacB/CdaS (Mehne et al, ), and CdaM (Blötz et al, ). Additionally, DAC activity has been demonstrated for a representative of the archaeal DacY/CdaZ class (Kellenberger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that c-di-AMP released by intracellular pathogens, such as Listeria monocytogenes and Mycobacterium tuberculosis, activates the hosts' immune system by triggering a type I interferon response (Woodward, Iavarone, & Portnoy, 2010;Yang et al, 2014). Amongst cyclic nucleotide-based second messengers, c-di-AMP has a unique position as it is (under standard growth conditions) the only second messenger that is essential for the vast majority of species that produce it (Blötz et al, 2017;Chaudhuri et al, 2009;Luo & Helmann, 2012;Song et al, 2005;Whiteley, Pollock, & Portnoy, 2015). In addition, the intracellular level of c-di-AMP needs to be tightly regulated as both decreased and increased amounts of c-di-AMP in the cytoplasm cause severe negative effects on the cells (Gundlach et al, 2015;Huynh & Woodward, 2016).…”
mentioning
confidence: 99%
“…Cyclic di-AMP (c-di-AMP) plays a central role in the adaptation of bacteria to the environmental osmolarity (Witte et al, 2008;Commichau et al, 2015Commichau et al, , 2018Commichau et al, , 2019Fahmi et al, 2017;Stülke and Krüger, 2020). c-di-AMP is in fact essential for Bacillus subtilis, Lactococcus lactis, Listeria monocytogenes and other Gram-positive bacteria (Woodward et al, 2010;Corrigan et al, 2011;Luo and Helmann, 2012;Bai et al, 2013;Mehne et al, 2013;Witte et al, 2013;Whiteley et al, 2015;Rismondo et al, 2016) since the dinucleotide prevents the uptake of potassium and other osmolytes to toxic levels by direct binding to the respective transport systems Bai et al, 2014;Kim et al, 2015;Schuster et al, 2016;Blötz et al, 2017;Gundlach et al, 2017;Whiteley et al, 2017;Devaux et al, 2018;Pham et al, 2018;Zarella et al, 2018;Zeden et al, 2018;Gibhardt et al, 2019;Gundlach et al, 2019;Quintana et al, 2019). Recently, it has been shown that c-di-AMP is also involved in osmoadaptation of cyanobacteria and archaea (Rubin et al, 2018;Braun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…M. tuberculosis produces only MtDisA, a DisA homolog (29). Mycoplasma pneumoniae produces only CdaM, which is closely related to the DAC domain of CdaS in B. subtilis (30). The Gram-positive pathogens S. pyogenes, S. pneumoniae, S. aureus, and L. monocytogenes produce only DacA, which is the most common c-di-AMP synthase among the four DAC enzymes discovered so far, as it is found in a wide variety of bacteria (10,12,31).…”
mentioning
confidence: 99%